1993
DOI: 10.1007/bf02048364
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of delayed hemorrhage following surgical hemorrhoidectomy

Abstract: Delayed hemorrhage following surgical hemorrhoidectomy is a well-recognized complication. Emergency treatment may include suture ligation, anal packing, or other means of tamponade. At the Lehigh Valley Hospital, 27 patients were seen with the complication of delayed hemorrhage over an eight-year period from 1983 to 1990, for an incidence of 0.8 percent. Twenty-five patients (93 percent) underwent surgery primarily for hemorrhoidal disease; one patient had hemorrhoids removed in addition to a sphincterotomy fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
25
1
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 2 publications
5
25
1
1
Order By: Relevance
“…Posthemorrhoidectomy secondary (referred to as late or delayed) hemorrhage occurs from several days to three weeks after surgery. 9,11,14 The reported rate ranges widely from 0.6 to 5.4 percent, 1-7 which correlates with the rate (0.9 percent) in this study. The treatment of PHSH remains controversial.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Posthemorrhoidectomy secondary (referred to as late or delayed) hemorrhage occurs from several days to three weeks after surgery. 9,11,14 The reported rate ranges widely from 0.6 to 5.4 percent, 1-7 which correlates with the rate (0.9 percent) in this study. The treatment of PHSH remains controversial.…”
Section: Discussionsupporting
confidence: 82%
“…[9][10][11] Rosen et al 11 suggested a rigid sigmoidoscopic examination to remove all blood and clots, followed by anal packing of Gelfoam ® wrapped by a topical hemostat to stop bleeding, 7 (35 percent) patients having complications and 15 percent of patients requiring a reoperation. Basso 15 claimed that all patients treated using tamponade with an inflated Foley catheter stopped bleeding instantaneously, and no secondary hemorrhage was inflicted by this procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bleeding was the most important with an incidence of 1.3%. Similar values are reported in the literature, with a range between 0.5 to 2.0% [8]. Although the spectrum of bleeding reported in the literature ranges from mild to severe life threatening bleeding requiring transfusions, all of our cases were promptly resolved only with ligation of the vascular pedicle, and none of our patients required a blood transfusion.…”
Section: Discussionsupporting
confidence: 90%
“…Tag mit einer Häufi gkeit von 0.8 %-2.5 % auf, besonders gefährdet sind Patienten, die unter Antikoagulantientherapie stehen [97,98]. Eine Injektion mit Adrenalin und/oder eine lokale Kompressionsbehandlung mit Gaze oder Ballonkatheter kann erfolgreich sein.…”
Section: Späte Nachblutungunclassified